Particularidades do trabalho feminino: um debate entre o patriarcado e a divisão sexual do trabalho - Bezerra, Ítala Carneiro (2014)
The women's work is still characterized by the devaluation and invisibility. Research on the subject focus on the productive work carried out by women, so there is little literature that discuss women's reproductive work. Our research attempts to grasp the female labor by double dimension of production and reproduction. Therefore, the analysis categories are worked patriarchy and the sexual division of labor. We seek to approach the reality of Brazilian workers in the last decade, through the literature review about this recent historical period. The survey has character of literature review and research of secondary data. As conclusions, we find that the female labor force retains some "stays" that seem to structure the condition of oppression / exploitation to which workers are subjected, such as the condition of precariousness in the production and social reproduction; inequality arising from the sexual division of labor characteristic of patriarchal capitalist mode of production. We also see some "changes" in the way of life, in which some indexes show improvements in the condition of the workers. In particular, in the last decade Brazilian, we realize that there has been no structural change, keeping up the rigidly divided market by the hierarchy between the sexes; however it was possible to see some changes, which although still incipient, visibilizam populations historically subordinated the Brazilian social dynamic. We realize as well that changes in female labor force is show significant due to the historical inequality of condition about segregation by sex, class, race / ethnic groups. On the varied precarious forms of women's work, indicated the growth of home work in the restructuring process as an aggravating sign of the capitalist offensive because it reinforces the status of domestic working women as it enables the reconciliation of productive work / reproductive. For this reason, the "leaving home", that is, the condition of paid working in a different room of the house shows how resistance naturalization of the female condition. We consider extremely important the possibility of mediation between the historical condition of women and the public space, which may represent the possibility of awareness of women regarding their condition of oppression and therefore confronting and overcoming this condition.